Empirical and Numerical Analysis of Bearing Capacity and Lateral Deflection of Pile in Tower-1 of Haji Hospital Medan - Hamzah, Rafika Riza; Roesyanto, Roesyanto; Harahap, Syiril Erwin (Jurnal Teknik Sipil, 2025)
The lateral bearing capacity of piles is a crucial factor in foundation design, particularly under lateral loads. This study analyzes the lateral bearing capacity of hydraulic jacked-in piles using the Broms method and interprets loading test results with the Chin and Mazurkiewicz methods. Additionally, numerical analysis of lateral deflection was conducted using the p-y method in LPile and the Finite Element Method (FEM) in PLAXIS 3D to assess compatibility with field test results. The results indicate that the lateral bearing capacity is 16,20 tons using the Broms method, 18,76 tons with the Chin method, and 16,50 tons with the Mazurkiewicz method. The lateral deflection at 200% load was 11,82 mm from field tests, 14,69 mm from LPile, 12,25 mm from PLAXIS 3D (Mohr-Coulomb), and 11,91 mm from PLAXIS 3D (HS Small). The HS Small model yielded the most accurate prediction, closely matching field test results. This research highlights the importance of numerical modeling in predicting lateral pile behavior and provides valuable insights for foundation design under lateral loads.